Reliability of concentric and eccentric strength of hip abductor and adductor muscles in young soccer players - Gerodimos, V.; Karatrantou, K.; Paschalis, V.; Zafeiridis, A.; Katsareli, E.; Bilios, P.; Kellis, S. (Biology of Sport, 2015)
The concentric and eccentric strength profile and muscular balance of the hip joint are important parameters for success in soccer. This study evaluated the reliability for the assessment of hip abduction and adduction isokinetic strength over a range of angular velocities (30 and 90°/s) and types of muscular actions (concentric and eccentric) in young soccer players. The reliability for the assessment of reciprocal (conventional and functional) and bilateral torque ratios was also examined. Fifteen male soccer players (15±1 years) performed two sessions, separated by three days. The testing protocol consisted of five maximal concentric and eccentric hip abductions and adductions of both legs at angular velocities of 30°/s and 90°/s. The peak torque was evaluated in young soccer players using an isokinetic dynamometer (Cybex Norm), and the reciprocal strength ratios (conventional and functional) and bilateral ratios (non-preferred to preferred leg ratios) were calculated. The test-retest reliability for the assessment of peak torque (ICC=0.71-0.92) and of reciprocal muscle group ratios (ICC=0.44-0.87) was found to be moderate to high. Bilateral torque ratios exhibited low to moderate reliability (ICC=0.11-0.64). In conclusion, isokinetic strength of hip abductor and adductor muscles and the conventional and functional strength ratios can be reliably assessed in young soccer players, especially at low angular velocities. The assessment, however, of bilateral strength ratios for hip abductor/adductor muscles should be interpreted with more caution.